2022
DOI: 10.3389/fpsyt.2022.1012850
|View full text |Cite
|
Sign up to set email alerts
|

The neuropeptide Y single-nucleotide polymorphism rs16147:T>C moderates the effect of alcohol dependence on depression in male Chinese Han population

Abstract: BackgroundPrevious studies suggest that alcohol dependence is associated with depression, however, the effect of alcohol dependence varies from individual to individual, which may be due to different genetic backgrounds. The interactions between alcohol dependence and different gene polymorphisms may finally shape the onset of depression. Neuropeptide Y (NPY), which can maintain homeostasis from high-stress stimulation, may protect individuals from the onset of depression. Here, we explored whether the NPY rs1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Consistent with previous studies (35,36), we found that anxiety and depression symptoms during withdrawal in AUD patients are highly correlated with alcohol dependence levels in withdrawal. There is an established relationship between alcohol and anxiety; high anxiety levels in AUD patients manifest during alcohol withdrawal (37-39).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies (35,36), we found that anxiety and depression symptoms during withdrawal in AUD patients are highly correlated with alcohol dependence levels in withdrawal. There is an established relationship between alcohol and anxiety; high anxiety levels in AUD patients manifest during alcohol withdrawal (37-39).…”
Section: Discussionsupporting
confidence: 92%
“…As indicated by the risk factor analyses, drinking behaviors may play a role in the susceptibility of female reproductive disorders linked to depression or dysthymia. Research has demonstrated a positive association between alcohol dependence and depression, indicating the potential involvement of interconnected neurobiological mechanisms 56 , 57 . It is widely recognized that alcohol negatively affects female reproduction 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated with G Power (3.1.9.2), according to the previous Gene × Environment studies where the differences of slope between different gene subgroups ranged from approximately 0.05–0.20. 23 , 24 Therefore, to conduct a linear regression with Δslope of 0.05, α value of 0.05 (two‐tailed), power of 0.95, the estimated sample size was 210 participants; that is, the sample size required for the study was 210 participants.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated with G Power (3.1.9.2), according to the previous Gene × Environment studies where the differences of slope between different gene subgroups ranged from approximately 0.05-0.20. 23,24 Therefore, to conduct a linear regression rs1477341 exhibited more depression symptoms. However, RETN rs3745368 had no significant interaction with alcohol dependence.…”
Section: Participantsmentioning
confidence: 99%